2017
DOI: 10.1016/j.jmau.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Causes of Pneumoperitoneum-induced Peritonitis: Results of an Empirical Study

Abstract: Pneumoperitoneum refers to presence of free air within the peritoneal cavity, “Pneumoperitoneum induced Peritonitis” is synonymous of surgical pneumoperitoneum, as the leak of air and visceral contents contaminates the peritoneal cavity, producing peritonitis which mandates surgery. This entire pneumoperitoneum may result from inflammatory conditions, traumatic injury, neoplasia, anastomotic leak and vascular causes.The objectives of this study is to determine the incidence of Pneumoperitoneum-induced Peritoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…These are only predictions because the blood culture at the time of peritonitis onset was negative but considering that the positivity rate of blood culture in biliary tract infections is only approximately 5%, 8 the estimation from the imaging findings is reasonable. Moreover, the previous report accessing the cause of peritonitis induced by the air leakage, which showed that air leakage of postoperative status, was the third common cause of the peritonitis, and the most common anatomical site of air leakage was gastroduodenal legion might support our opinion 9 …”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…These are only predictions because the blood culture at the time of peritonitis onset was negative but considering that the positivity rate of blood culture in biliary tract infections is only approximately 5%, 8 the estimation from the imaging findings is reasonable. Moreover, the previous report accessing the cause of peritonitis induced by the air leakage, which showed that air leakage of postoperative status, was the third common cause of the peritonitis, and the most common anatomical site of air leakage was gastroduodenal legion might support our opinion 9 …”
Section: Discussionsupporting
confidence: 76%
“…Moreover, the previous report accessing the cause of peritonitis induced by the air leakage, which showed that air leakage of postoperative status, was the third common cause of the peritonitis, and the most common anatomical site of air leakage was gastroduodenal legion might support our opinion. 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2021] Some larger retrospective studies have reported findings of pneumoperitoneum in 5%–8% of gastrointestinal perforations due to perforated appendicitis. [2223] In 23 patients evaluated with abdominal/chest X-ray, we found the frequency of pneumoperitoneum in 3 (13%) cases. A higher value obtained in this study may be attributed to the estimation of frequency of pneumoperitoneum in cohorts of patients under review, rather than the etiology of pneumoperitoneum in acute abdomen which was evaluated in most studies.…”
Section: Discussionmentioning
confidence: 93%
“…A higher value obtained in this study may be attributed to the estimation of frequency of pneumoperitoneum in cohorts of patients under review, rather than the etiology of pneumoperitoneum in acute abdomen which was evaluated in most studies. [2223] The clinical diagnosis and indications for surgery in most of our patients were based mainly on the history and clinical signs of peritonitis. Positive radiological signs of perforation such as pneumoperitoneum were added reinforcement to our diagnosis and our decision to operate.…”
Section: Discussionmentioning
confidence: 99%